Katanin subunits p60 and p80, potential biomarkers for papillary thyroid carcinoma to distinguish nodular goiter: STROBE - Zhangming Wu, Msc; Miao Guo, MD; Jing Yang, MD, PhD; Yanjie Xiao, MD; Wei Liu, MD, PhD (Medicine, 2022)
Abstract. Katanin subunits p60 and p80 are involved in microtubule-mediated cytoskeletal organization during cell division. Their aberrant expression has been found in prostate, breast, and non-small cell lung (NSCLC) cancers. It has recently been reported that compared with adjacent papillary thyroid carcinoma (PTC) tissues, both are highly expressed in tumor tissues. Here, we investigated whether katanin subunits p60 and p80 can be used as potential biomarkers for PTC to distinguish nodular goiter (NG). Immunohistochemistry was performed to investigate the expression of katanin subunits p60 and p80 in the tissues of 97 cases of PTC and NG. This cohort included 87 cases with PTC (74 classical or conventional (CPTC) and 13 follicular (FVPTC) variants) and 10 cases with NG. We found that katanin subunits p60 and p80 were expressed in PTC, but not in NG. The cutoff values of katanin p60 and p80 for PTC were 22.43% and 0.83%, respectively. The katanin subunit p60 was significantly associated with lymph node metastasis. Katanin subunit p80 was more highly expressed in CPTC than in FVPTC. The expression of the katanin subunit p60 was positively correlated with the expression of katanin p80 in PTC. Importantly, we found that overexpression of katanin p60 increased the expression of katanin p80 in a human papillary thyroid carcinoma KTC-1 cell line, which further supports the existence of katanin p60 and p80 feedback loops. Our results indicate that katanin subunits p60 and p80 may be used as potential PTC biomarkers to distinguish NG and may be novel therapeutic targets for PTC.